Discours sur le développement durable : virages, tensions et conséquences pour le secteur forestier chilien - Enrique Aliste; Daniela Cea; Mauricio Folchi (Cahiers des Amériques Latines)
Society-nature relations in Latin America have always been strained from the discourses of development. The notions that seek to install the idea of a development that is based especially on the exploitation of the natural resources, has led for decades the debate circulates between the strategies that have tended to the search of the development of the industry, to strengthen the productive capacities, to incorporate added value, among others. These discourses have occupied great spaces in the debate of the public policies and of the intellectual production, giving rise to positions and schools that have allowed a rich flow of ideas around the subject. However, these same strategies have served to carry forward practices and processes in industries whose sustainability is questionable or at least, as arguable as the forest sector, especially in Chile.